OUTCOMES OF TREATMENT OF PATIENTS WITH CHRONIC TUBOTYMPANIC OTITIS MEDIA USING VENTILATION TUBES - Гринько, І.І. (World of Medicine and Biology, 2017)
Adequate function of the Eustachian tube (ET) is one of the main conditions for successful treatment of patients with chronic tubotympanic suppurative otitis media. In patients with 5th grade ET dysfunction tympanoplasty was performed using Teflon and silicon ventilation tubes (VT). When the ET function was improved (improving from 5th grade to 1st – 4th grade), ventilation tube was removed. After the removal of VT, the condition of neotympanic membrane was evaluated by otomicroscopy and tympanometry. Among the 49 patients whom tympanoplasty was performed using VT in 96.0 % cases, the 5th grade was diagnosed. After 3 months, 5th grade was detected in 63.3 % of cases, after 6 months in 20.4 % of cases, after 12 months in 4.1% of cases. Tympanometry in patients after VT removement in 6 months shows tympanogram type "A" in 8.2 % of cases, type "B" in 32.7 % of cases, type "C" in 8.2 % of cases. In 12 months after tympanoplasty, type "A" was detected in 57.1 % of cases, type "B" in 20.4 % of cases, type "C" in 10.2 % of cases. Dynamics of the epidermisation of the neotympanic membrane shows decrease number of patients with incomplete epidermisation at 3, 6, 12 months (72.9 %, 21.3 %, 0 %). In dynamics of observation increasing number of cases with complete epidermis at 3, 6, 12 months (27.1 %, 74.5 %, 89.5 %) was detected. Recurrent perforation of the neotympanic membrane was observed in 10.5 % of cases among patients with a 5th grade ET dysfunction.
Keywords: сhronic otitis; timpanometry; dysfunction of the auditory tube; timpanoplasty